Innovation Learning Mathematics : Student Worksheets Based on Realistic Mathematics Education as a Solution for Increase Ability Literacy Numeracy and Productive Struggle Student Grade 5 Elementary School - Mufliva, Rosiana; Hafshah, Destiana Dewi; Effendy, Amanda Fauziah Mifa; Zahrah , Anggita Zuniatu; Rinata, Vira; Khoirunnisa (International Conference on Elementary Education, 2025)
Research This motivated by the existence of misconceptions experienced student Grade 5 of elementary school in learning Least Common Multiple consequence no the maximum use book eye lesson Mathematics and its unavailability Worksheets Student based on RME which can support activity student in effort reach objective appropriate learning with task development and needs students, so that impact on lowering ability literacy numeracy students. Purpose study This is Develop Worksheets Students on the material Least Common Multiple in 5th grade elementary school, obtain description Eligibility of Worksheet Student RME based, obtain description improvement ability literacy numeracy students and describe productive struggle student to Use of Worksheets Student based on RME. In this study This data collection was carried out with use method test in the form of giving pre-test and posttest and tested in a way quantitative through n-gain test for know improvement ability literacy numeracy students and non- test methods in the form of analyzed questionnaire in a way qualitative. Research This using the ADDIE model which has five stages that is Analyze, Design, Development, Implementation, Evaluation. The results are as follows research obtained that is Worksheet development Student based on RME using the ADDIE model, the results of the feasibility test teaching materials based on results expert review material eye lesson by 97.5% with very good qualification, results expert review design learning by 95% with very good qualification, results practitioner review learning by 92.5% with very good qualification, response participant educate by 95% with very good qualifications . Improvement ability literacy mathematically also shown student with score n-gain of 0.67 with category medium. Response results productive struggle student is of 2.91 which is in the category in progress. Research This show that Worksheet Student RME based on materials Least Common Multiple This worthy used and can increase ability literacy mathematical and productive struggle of students . Conclusion from study This is a Worksheet Student based on this RME approach can used for help participant educate 5th grade elementary school construction ability literacy mathematical student about Least Common Multiple And make productive struggle student is at a moderate level.